Neocryptolepine (cryprotackieine), a unique bioactive natural product: Isolation, synthesis, and profile of its biological activity - Bracca, Andrea Beatriz Juana (2014)
The widely varying different approaches to the total synthesis of the indoloquinoline alkaloid neocryptolepine are discussed. Aspects relating to the isolation of the natural product from Cryptolepis sanguinolenta, as well as its performance in various biological tests and spectroscopic studies involving the natural product, are also reviewed.